Do Not Tape Over: AIDS Activist Videos in the United Kingdom - Ed Webb-Ingall (British Art Studies)
This article presents a selection of AIDS activist videos to explore the impact of HIV/AIDS on activist methods and artistic production in Britain in the 1980s and early 1990s. It attempts to redress a gap in the history of moving-image production and distribution in the United Kingdom by those who were impacted by HIV/AIDS. It shows that AIDS activist videos employed a multiplicity of approaches to production and distribution, each responding to a specific context or subject position. It explores how such films were made in the context of failures of representation, and an absence of self-expression, in mainstream media; and identifies key differences between AIDS activist production and distribution in the United Kingdom and the United States.